Parenting Styles And Gaming Duration In Adolescent Mental Health: A Cross-Sectional Study In Banten, Indonesia - Riyanto, Dwi Agung (Journal of Applied Nursing and Health, 2025)
Background: A national survey in Indonesia found that one in three adolescents faces mental health issues, with one in 20 diagnosed with a mental disorder in the past year. This study examines the relationship between online gaming duration, parenting styles, and adolescent mental health at SMA Negeri 1 Leuwidamar, Banten. Findings suggest that gaming dependence, especially with violent content, may trigger aggression and reduce social interaction. Policy recommendations include parental education on gaming impacts, time management, and promoting extracurricular activities, with schools collaborating to support adolescent mental well-being. Methods: This study employs a correlational design with a cross-sectional approach. It develops instruments concerning mental health and parenting styles to minimise memory distortion, utilising specific questions and allowing sufficient time for responses. Individuals conducted data collection without bias towards the hypotheses. The research population consists of all students in grades X and XI at SMA Negeri 1 Leuwidamar, totalling 494 students. The criteria for respondents are students in grades X and XI who enjoy online gaming, are in good health during data collection, and possess functioning devices. A sample of 91 respondents was selected from the population using purposive sampling.. Results: The findings reveal that nearly half of the respondents, specifically 48 individuals (52.7%), experience mental health issues. Additionally, the majority of respondents, 65 individuals (71.4%), spend more than 2 hours per day playing online games, and 51 individuals (56.0%) exhibit a democratic parenting style. Statistical tests indicate a significant relationship between the duration of online gaming and adolescent mental health, with a p-value of < 0.001, as well as between parenting styles and adolescent mental health, also with a p-value of < 0.001. Conclusion: This study underscores a significant interaction between the time spent on online gaming and parenting methods affecting the mental health of adolescents at SMA Negeri 1 Leuwidamar. The increasing dependence on online gaming complicates parenting challenges. Consequently, collaboration between schools and parents is essential to foster a supportive environment for mental health. Schools are advised to formulate policies regarding smartphone usage, while parents are encouraged to engage more actively in their children's education with a supportive approach.